Predicting personalized mathematics learning among pre-university students in the Maldives - Mohamed, Mausooma; Ayub, Ahmad Fauzi Mohd; Yasin, Maizura; Nawi, Nur Raihan Che (Institute of Advanced Engineering and Science, 2025)
The use of learning management systems (LMS), such as Moodle, for personalized mathematics learning (PML) is successful; nonetheless, its performance depends on several factors. This study investigates the factors influencing the utilization of LMS for PML at the Maldives National University (MNU). A correlational study was conducted involving 120 randomly selected pre-university students using an online questionnaire to measure performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), and student commitment (SC) toward LMS usage behavior (UB). Data analysis with IBM statistical package for the social sciences (SPSS) statistics version 25.0 revealed significant positive relationships between LMS UB and PE (r=0.624**), EE (r=0.644**), FC (r=0.533**), and SC (r=0.696**), with SC being the strongest predictor. SI showed a weaker positive relationship (r=0.204). The study also discovered a multiple correlation (R) value of 0.807 and an analysis of variance (ANOVA) (F (5, 114)=42.497, p=0.000). The study’s findings underscore the significance of these factors in promoting LMS adoption and effective use concluding that focusing on these key predictors can enhance PML and improve student engagement and performance.